Placental dimethyl acetal fatty acid derivatives are elevated in preeclampsia. (March 2017) - Brien, M.; Berthiaume, L.; Rudkowska, I.; Julien, P.; Bilodeau, J.F.
Abstract: Preeclampsia (PE) was shown to affect the placental content and the transfer of polyunsaturated fatty acids (PUFA) to the fetus. Plasmalogens, a type of phospholipids with a vinyl-ether link at the sn-1 position, play an antioxidant role and are specifically enriched in PUFA at the sn-2 position. In this study, we characterized plasmalogen-derived dimethyl acetal (DMA) fatty acid derivatives, 16:0 DMA, 18:0 DMA, 9 c -/11 c -18:1 DMA and PUFA in the placenta of normotensive (n = 20) and PE (n = 20) pregnancies, according to the sampling site: peri-insertion or periphery. Phospholipid fatty acids from the placenta and maternal erythrocytes were identified by gas chromatography mass spectrometry and quantified by flame ionization detection. We found elevated total DMA in the PE placenta by 18% when compared to normotensive controls (p = 0.026). Moreover, the 16:0 DMA account for more than 55% of DMA fatty acids measured in the placenta, and its level is significantly higher in PE than controls (p = 0.018). Also, we found elevated placental PUFA, 20:5(n-3), 22:5(n-3) and a low level of 20:4(n-3) in PE compared to controls. Placental DMA was highly correlated with n-6 and n-3 PUFA in both, normotensive and PE pregnancies. In sum, elevated DMA fatty acids in the PE placenta could be an indirect defensive mechanism against oxidative stress and poor placental fatty acid transfer in PE. Highlights: Dimethyl acetal (DMA) fatty acid derivatives were assessed in the placental villi. DMA fatty acids are elevated in preeclampsia. Placental DMA fatty acids are correlated with polyunsaturated fatty acids.